The Unbearable Lightness of Being a Copula in Latin: on a Textual Problem in Cicero’s Oration „In Defence of Publius Sestius” - Jakielaszek, Jarosław (Research in Language, 2007)
A textual problem from Cicero’s oration In defence of Publius Sestius is discussed in order to determine syntactic and semantic consequences of editorial choices. The discussion involves semantic and syntactic properties of Latin past participles within a minimalist setting. A detailed investigation of the passage indicates that a textual variant not accepted by most editors is to be preferred.